Strategi Pelaksanaan Program Pemulihan Ekonomi Nasional Pada Kantor Pusat PT. Bank Sulselbar - Iswadi Amiruddin; Nursaleh Hartaman (Jayapangus Press, 2022)
This study purposed to find out the implementation strategy of the National Economic Recovery program at the Head Office of PT. Bank Sulselbar using qualitative research methods, the number of informants was 10 people. The results of the study showed that 1) objectives (realization of goals, objectives and targets) by appointing divisions, setting targets, forming a special program, namely increasing the productive loan portfolio of the MSME segment. Obstacles to be overcome included credit to new debtors, low purchasing power in the Covid-19 era, credit period of only 6 months, decreased growth, implementation of Large-Scale Social Restrictions (PSSB), physical distancing and social distancing, business actors who saw economic growth conditions. 2) the method was to make the distribution of guidelines for PEN funds Number SR/072/DRK/VIII/2022, increase the consumer credit portfolio, productive for the corporate and syndicated segments. 3) facilities, namely completing facilities consisting of branch offices, facilities, social media, the use of mass media and establishing MSME Centers to empower business groups and foster MSMEs which were expected to synergize.